Metastatic Clear Cell Renal Cell Carcinoma to Pancreas and Distant Organs 24 Years After Radical Nephrectomy: A Case Report and Literature Review - Cao, Huawei; Sun, Zejia; Wu, Jiyue; Hao, Changzhen; Wang, Wei (Frontiers in Surgery, 2022)
Background: Clear cell renal cell carcinoma (CCRCC) is a common urological neoplasm, and even though surgical resection is effective for localized CCRCC, the prognosis of metastatic CCRCC is poor. Currently, there is a paucity of recognized effective therapeutic protocols for metastatic CCRCC. Case presentation: A 76-year-old Asian man underwent radical left nephrectomy for CCRCC 26 years ago; this patient visited our hospital with abdominal pain due to multiple abdominal metastases 24 years after the nephrectomy. After metastasectomy, he underwent targeted therapy combined with a programmed death receptor-1 (PD-1) inhibitor, and the current imaging results indicate remarkable tumor remission. Conclusions: Metachronous pancreatic metastasis from CCRCC after nephrectomy is rare, but clinicians and patients should not ignore this possibility. The combination of targeted therapy and immunotherapy can result in satisfactory outcomes in cases where metastatic CCRCC continues to progress despite metastasectomy and targeted therapy. The combination of local and systemic therapy can be an effective therapeutic protocol for metastatic CCRCC, but there is no consensus on suitable therapeutics.